Unilateral agenesis of the right ovary and Fallopian tube in an infertile patient with a normal uterus - Rudić Biljić Erski, Ivana; Vasiljević, Mladenko; Rakić, Snežana; Mihajlović, Sladjana (Vojnosanitetski pregled, 2021)
Introduction. Unilateral ovarian and Fallopian tube agenesis is an extremely rare anomaly that is usually associated with uterine and renal anomalies. This anomaly is usually incidentally detected during laparoscopy or laparotomy performed for other indications. We have reported a rare case of unilateral ovarian and Fallopian tube agenesis in an infertile patient with a normal uterus. Case report. A 34-year-old infertile patient was admitted to our clinic for laparoscopy and hysteroscopy, indicated for the right Fallopian tube occlusion and an endometrial polyp. The patient underwent laparoscopy and hysteroscopy. Unilateral right ovarian and Fallopian tube agenesis was diagnosed during laparoscopy. Upon exploration of peritoneal surfaces, omentum and intestinal serosa, neither ectopic nor remnant tissues of the ovary or Fallopian tube were found. Renal anomalies were not identified on the ultrasound examination. The hormone panel and karyotype were normal. Her partner’s semen analysis was normal. The patient conceived spontaneously one year later. Serial ultrasound examinations showed normal fetal intrauterine growth and development. The patient vaginally delivered a live, female newborn at 40 weeks’ gestation, weighing 3,350 grams, 53 cm long, with 9/10 Apgar scores at birth. The patient and her newborn were discharged home on the third postpartum day. Conclusion. Unilateral ovarian and Fallopian tube agenesis is rarely associated with a normal uterus. Laparoscopy is the gold standard in the diagnosis of ovarian and Fallopian tube agenesis. Unless other obstetric indications are present, this anomaly is not specific and it is not an indication for a Caesarean section, and vaginal delivery is a possibility at term pregnancy.